2016
DOI: 10.1017/s0029665115004498
|View full text |Cite
|
Sign up to set email alerts
|

The Sleep-E Study: An on-going cross-sectional study investigating associations of sleep quality and cardio-metabolic risk factors

Abstract: Short sleep duration (⩽5-6 h/night) has been associated with an increased risk of weight gain (1,2) and non-communicable disease (3). Recently, through a systematic review and meta-analysis, we identified that short sleep duration may induce positive energy balance and have implications on weight gain over the long term (Al Khatib et al, unpublished data). Quality of sleep, opposed to its duration, has not been extensively reported in the context of the impact on disease risk. While self-reported measures of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…Jakubowicz et al found similar results in 93 women with overweight or obesity and showed beneficial effects of high caloric intake at breakfast compared with in the evening in terms of weight loss, waist circumference, serum ghrelin and lipids, appetite scores and insulin resistance indices (Jakubowicz et al, 2013). Other studies have shown the importance of meal frequency and/ or meal irregularity for cardiometabolic health (Farshchi et al, 2004;Farshchi et al, 2005;Madjd et al, 2016;Pot et al, 2016).…”
Section: Biological Clock: Underlying Mechanismsmentioning
confidence: 78%
See 2 more Smart Citations
“…Jakubowicz et al found similar results in 93 women with overweight or obesity and showed beneficial effects of high caloric intake at breakfast compared with in the evening in terms of weight loss, waist circumference, serum ghrelin and lipids, appetite scores and insulin resistance indices (Jakubowicz et al, 2013). Other studies have shown the importance of meal frequency and/ or meal irregularity for cardiometabolic health (Farshchi et al, 2004;Farshchi et al, 2005;Madjd et al, 2016;Pot et al, 2016).…”
Section: Biological Clock: Underlying Mechanismsmentioning
confidence: 78%
“…First, they demonstrated in a systematic review and meta‐analysis of human intervention studies that partial sleep deprivation resulted in increased energy intake but not increased energy expenditure, leading to a net positive energy balance of 385 kcal/day (Al Khatib et al, 2017). Subsequently, they showed in a pilot cross‐sectional study ( Sleep‐E study) that sleep quality is linked to lipid metabolism (Al Khatib et al, 2016). Lastly, they showed that sleep extension is a feasible lifestyle intervention in free‐living, habitual short sleepers in a randomised controlled trial ( SLuMBER study) (Al Khatib et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep-E is a pilot cross-sectional study to investigate the association between energy balance, dietary intake, cardio-metabolic risk factors and body composition with objective measures of sleep duration and quality in healthy adults (Al Khatib et al 2016b). We hypothesised that short sleep duration and/or poor sleep quality would be associated with higher EI and poorer diet quality and habits.…”
Section: The Sleep-e Studymentioning
confidence: 99%